2010
DOI: 10.2478/v10098-010-0006-0
|View full text |Cite
|
Sign up to set email alerts
|

On the use of the simple scaling of heavy rainfall in a regional estimation of IDF curves in Slovakia

Abstract: The aim of this study was to test the applicability of a simple scaling methodology for a regional estimation of intensity-duration-frequency (IDF) curves in Slovakia. The analysis is based on the regionalization process of Gaál (2006), which focused on the delineation of homogeneous regions for a regional frequency analysis of precipitation maxima. In order to examine the regionally estimated IDF curves, a region covering the western parts of Slovakia was chosen. The selected region, which encompasses 19 rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
1
18
0
2
Order By: Relevance
“…For instance, Menabde et al (1999) compared two sets of rainfall data representing two examples of quite different climate types, and found a scaling exponent of À0:65 for Melbourne (Australia), a city with a mid-latitude temperate climate and rainfall throughout the year, and a value of À 0:76 for Warmbaths (South Africa), having a semiarid climate with summer convective rainfall, and concluded that the scaling exponent appears to be dependent on the rainfall/climate characteristics. In addition, Bara et al (2009) found scaling exponents around -0.75 for three locations representing the western (Kuchyňa-Nový Dvor), central (Liptovský Hrádok), and eastern (Humenné) areas of Slovakia, and Yu et al 2004found three types of rainfall scaling behavior over northern Taiwan, related to the change in topography and the influence of the northeast monsoon. Rodríguez-Solà et al (2017) found a general concordance between the spatial distribution of b over the Iberian Peninsula and the mean annual precipitation distribution, with high values between -0.55 and -0.66 in rainy areas and low between -0.84 and -0.92 for the dry ones, with some discrepancies related to the kind of precipitation contributing to high rainfall amounts and the proportion of convective rainfall in total.…”
Section: The Simple Scaling Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Menabde et al (1999) compared two sets of rainfall data representing two examples of quite different climate types, and found a scaling exponent of À0:65 for Melbourne (Australia), a city with a mid-latitude temperate climate and rainfall throughout the year, and a value of À 0:76 for Warmbaths (South Africa), having a semiarid climate with summer convective rainfall, and concluded that the scaling exponent appears to be dependent on the rainfall/climate characteristics. In addition, Bara et al (2009) found scaling exponents around -0.75 for three locations representing the western (Kuchyňa-Nový Dvor), central (Liptovský Hrádok), and eastern (Humenné) areas of Slovakia, and Yu et al 2004found three types of rainfall scaling behavior over northern Taiwan, related to the change in topography and the influence of the northeast monsoon. Rodríguez-Solà et al (2017) found a general concordance between the spatial distribution of b over the Iberian Peninsula and the mean annual precipitation distribution, with high values between -0.55 and -0.66 in rainy areas and low between -0.84 and -0.92 for the dry ones, with some discrepancies related to the kind of precipitation contributing to high rainfall amounts and the proportion of convective rainfall in total.…”
Section: The Simple Scaling Approachmentioning
confidence: 99%
“…Applying this scaling approach, Aronica and Freni (2005) found better results than those coming from the classical subhourly rainfall regression formulas (Bell 1969;Ferreri and Ferro 1990). Likewise, studying the scaling properties of selected rainfall quantiles and applying this methodology, Bara et al (2009) derived the IDF curves for durations shorter than a day, calculated from a historical data set covering the whole territory of Slovakia. In a recent paper, Rodríguez-Solà et al (2017) used this methodology also to reproduce the well-known empirical IDF curves of three Spanish locations: Barcelona (Casas et al 2004;Rodríguez et al 2014), the Ebre Observatory (Pérez-Zanón et al 2015), and Madrid (Casas-Castillo et al 2016), taking into consideration the scaling behavior of rainfall.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies comparing methodologies have been conducted but generally all methods seem to be able to produce accurate IDF estimates (Mohymont et al 2004;Veneziano et al 2007;Dame et al 2008). The type I extreme value, (EVI or Gumbel) distribution has been used successfully in many recent rainfall intensity studies in Europe (Llasat 2001;Bara et al 2010;Olsson et al 2012), Asia (Ariff et al 2012;Ben-Zvi 2009; Ahammed and Hewa 2012), Africa (Kuo et al 2013;Mohymont et al 2004) and America (Lumbroso et al 2011;Pizarro et al 2012). EVI is currently the recommended distribution function for use in Canada and the best choice for the estimation of IDF curves under changing climate conditions (Das et al 2013).…”
Section: Intensity-duration-frequency Curvesmentioning
confidence: 99%
“…Such in most locations rainfall data are usually available only from totaliser rain gauges registering 1‐day precipitation, a method to infer intensity‐frequency values for short durations from daily rainfall data can be very useful. There is a methodology based on the fractal properties of rainfall, or more specifically on the characteristic scale invariance of the fractal processes (Bendjoudi et al , ; De Michele et al , ; Yu et al , ), to obtain the disaggregation or downscaling of low resolution precipitation data (daily) to high resolution (sub‐daily) (Menabde et al , ; Desramaut, ; Bara et al , ). Many atmospheric processes produced by complex dynamic mechanisms acting in a wide temporal range, as rainfall generation, give rise to phenomena that look the same regardless the scale where they are contemplated (self‐similarity).…”
Section: Introductionmentioning
confidence: 99%